Masters and their material - Wilder, Adelaide Frances (My University, 1898)
Introduction: The student of General History who glances back over the past finds names which stand out in prominence, representing a host of mighty leaders in every department of life, statesmen, warriors, reformers, scientific investigators, inventors, artists, and musicians. Many of these men lived and died without knowing they were leaders destined to change the current of some political or social gulfstream so that the lives of individuals and nations should be turned into new channels by their expressed thoughts or deeds. They worked at the very same problems over which the people of today are working. They were hungry, or cold, perplexed, or made glad over the very things that annoy or make glad the world today. They sacrificed to win the goal for which they were striving just as the world has to strive for the same success in this age. Sometimes these great masters failed to reach the point for which they set out but their very failure of highest success may have done as much for the world in the way of warning as it would have done if they had won and others been encouraged. The men of this age ought to be greater than the men of earlier ages for they have the examples of success and failure which ought to help to win the prize or prevent repeating the mistake of others.
Citation: Wilder, Adelaide Frances. Masters and their material. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: History; Warriors; Reformers; Political; Social Gulfstream; Theses; Manuscripts (documents)